A comparative analysis of lung function and spirometry parameters in genotype-controlled natives living at low and high altitude - Esteban Ortiz-Prado; Sebastián Encalada; Johanna Mosquera; Katherine Simbaña-Rivera; Lenin Gomez-Barreno; Diego Duta; Israel Ochoa; Juan S. Izquierdo-Condoy; Eduardo Vasconez; German Burgos; Manuel Calvopiña; Ginés Viscor (BMC Pulmonary Medicine)
Abstract Background The reference values for lung function are associated to anatomical and lung morphology parameters, but anthropometry it is not the only influencing factor: altitude and genetics are two important agents affecting respiratory physiology. Altitude and its influence on respiratory function has been studied independently of genetics, considering early and long-term acclimatization. Objective The objective of this study is to evaluate lung function through a spirometry study in autochthonous Kichwas permanently living at low and high-altitude. Methodology A cross-sectional study of spirometry differences between genetically matched lowland Kichwas from Limoncocha (230 m) at Amazonian basin and high-altitude Kichwas from Oyacachi (3180 m) in Andean highlands. The sample size estimates permitted to recruited 118 patients (40 men and 78 women) from Limoncocha and 95 (39 men and 56 women) from Oyacachi. Chi-square method was used to analyze association or independence of categorical variables, while Student’s t test was applied to comparison of means within quantitative variables. ANOVA, or in the case that the variables didn’t meet the criteria of normality, Kruskal Wallis test were used to compare more than two groups. Results The FVC and the FEV1 were significantly greater among highlanders than lowlanders (p value < 0.001), with a proportion difference of 15.2% for men and 8.5% for women. The FEV1/FVC was significantly higher among lowlanders than highlanders for men and women. A restrictive pattern was found in 12.9% of the participants. Conclusion Residents of Oyacachi had greater FVC and FEV1 than their peers from Limoncocha, a finding physiologically plausible according to published literature. Lung size and greater ventilatory capacities could be an adaptive mechanism developed by the highlander in response to hypoxia. Our results support the fact that this difference in FVC and FEV1 is a compensatory mechanism towards lower barometric and alveolar partial pressure of oxygen pressure.